Decreased breathing variability is associated with poorer outcome in mechanically ventilated patients - Camille Rolland-Debord; Tymothee Poitou; Come Bureau; Isabelle Rivals; Thomas Similowski; Alexandre Demoule (ERJ Open Research, 2023)
Rationale Breathing is a cyclic activity that is variable by nature. Breathing variability is modified in mechanically ventilated patients. We aimed to evaluate whether decreased variability on the day of transition from assist-control ventilation to a partial mode of assistance was associated with a poorer outcome. Methods This was an ancillary study of a multicentre, randomised, controlled trial comparing neurally adjusted ventilatory assist to pressure support ventilation. Flow and the electrical activity of the diaphragm (EAdi) were recorded within 48 h of switching from controlled ventilation to a partial mode of ventilatory assistance. Variability of flow and EAdi-related variables were quantified by the coefficient of variation, the amplitude ratio of the spectrum's first harmonic to its zero-frequency component (H1/DC) and two surrogates of complexity. Main results 98 patients ventilated for a median duration of 5 days were included. H1/DC of inspiratory flow and EAdi were lower in survivors than in nonsurvivors, suggesting a higher breathing variability in this population (for flow, 37% versus 45%, p=0.041; for EAdi, 42% versus 52%, p=0.002). By multivariate analysis, H1/DC of inspiratory EAdi was independently associated with day-28 mortality (OR 1.10, p=0.002). H1/DC of inspiratory EAdi was lower in patients with a duration of mechanical ventilation <8 days (41% versus 45%, p=0.022). Noise limit and the largest Lyapunov exponent suggested a lower complexity in patients with a duration of mechanical ventilation <8 days. Conclusion Higher breathing variability and lower complexity are associated with higher survival and lower duration of mechanical ventilation.